2005
DOI: 10.1158/1078-0432.ccr-04-2469
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells in Breast Cancer: Correlation to Bone Marrow Micrometastases, Heterogeneous Response to Systemic Therapy and Low Proliferative Activity

Abstract: Purpose: The incidence and biological characteristics of circulating tumor cells in the blood of patients with breast cancer were examined and subgroups were evaluated in the context of systemic treatment and the presence of disseminated tumor cells in bone marrow. Experimental Design: Circulating tumor cells were isolated from the peripheral blood of patients with breast cancer using a gradient system designed for the enrichment of circulating tumor cells (OncoQuick). Circulating tumor cells were identified w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
247
2
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 369 publications
(271 citation statements)
references
References 32 publications
(29 reference statements)
14
247
2
8
Order By: Relevance
“…It has been shown that CTCs have a half-life of 1 -2.4 h (Meng et al, 2004) and are nonreplicating (Muller et al, 2005) and that these must be replenished by replicating cells from elsewhere. Potentially, this could be the bone marrow; however, the DTCs, when in the bone marrow, are also non-replicating in the majority of primary breast cancer patients (Pantel et al, 1993;Muller et al, 2005). In each case, we have used the best available methodologies for detecting the cells and further studies on a larger cohort of patients along with improvements in assays, for example, CellSearch applied to bone marrow aspirates, may improve the correlation between CTCs and DTCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CTCs have a half-life of 1 -2.4 h (Meng et al, 2004) and are nonreplicating (Muller et al, 2005) and that these must be replenished by replicating cells from elsewhere. Potentially, this could be the bone marrow; however, the DTCs, when in the bone marrow, are also non-replicating in the majority of primary breast cancer patients (Pantel et al, 1993;Muller et al, 2005). In each case, we have used the best available methodologies for detecting the cells and further studies on a larger cohort of patients along with improvements in assays, for example, CellSearch applied to bone marrow aspirates, may improve the correlation between CTCs and DTCs.…”
Section: Discussionmentioning
confidence: 99%
“…25,48 However, CTCs may play a major role in the evaluation of therapeutic efficacy because of their easier accessibility compared with bone marrow. 49,50 Currently, only 1 system for the detection of CTCs (CellSearch TM assay; Veridex) has received clearance from the U.S. Food and Drug Administration. That system has demonstrated the ability to deliver clinically relevant information for CTC detection in a prospective trial: It visualizes CTCs by using immunofluorescent micro- The presence of disseminated tumor cells in the bone marrow from patients with no evidence of disease after definitive primary and adjuvant therapy is associated with poor outcome.…”
Section: Perspectives and Unsolved Problems For The Clinical Utility mentioning
confidence: 99%
“…Over the past few years, different approaches for the detection, enumeration and isolation of CTCs in blood have been developed. Immunocytochemical analysis is usually used in combination with density-gradient centrifugation (Balic et al, 2005;Muller et al, 2005;Wiedswang et al, 2006), size filtration (Kahn et al, 2004;Wong et al, 2006) or flow cytometry (Meng et al, 2004;Allan et al, 2005) to enrich tumour cells before their detection. In addition, nucleic-acid-based approaches for cell detection have been described (Lambrechts et al, 1999;Smith et al, 2000;Aerts et al, 2001;Stathopoulou et al, 2002;Benoy et al, 2004).…”
mentioning
confidence: 99%